Engineering of Transition Metal Catalysts Confined in Zeolites - Kosinov, Nikolay; Liu, Chong; Hensen, Emiel J M; Pidko, Evgeny A (Chemistry of materials, 2018)
Transition metal-zeolite composites are versatile catalytic materials for a wide range of industrial and lab-scale processes. Significant advances in fabrication and characterization of well-defined metal centers confined in zeolite matrixes have greatly expanded the library of available materials and, accordingly, their catalytic utility. In this review, we summarize recent developments in the field from the perspective of materials chemistry, focusing on synthesis, postsynthesis modification, (operando) spectroscopy characterization, and computational modeling of transition metal-zeolite catalysts.